A Systematic Review on Cannabinoids for Neuropathic Pain Administered by Routes Other than Oral or Inhalation - Jose-Manuel Quintero; German Pulido; Luis-Fernando Giraldo; Marta-Ximena Leon; Luis-Eduardo Diaz; Rosa-Helena Bustos (Plants, 2022)
The use of cannabis and cannabinoid products for the treatment of neuropathic pain is a growing area of research. This type of pain has a high prevalence, limited response to available therapies and high social and economic costs. Systemic cannabinoid-based therapies have shown some unwanted side effects. Alternative routes of administration in the treatment of neuropathic pain may provide better acceptance for the treatment of multiple pathologies associated with neuropathic pain. To examine the efficacy, tolerability, and safety of cannabinoids (individualized formulations, phytocannabinoids, and synthetics) administered by routes other than oral or inhalation compared to placebo and/or conventional medications in the management of neuropathic pain. This systematic review of the literature reveals a lack of clinical research investigating cannabis by routes other than oral and inhalation as a potential treatment for neuropathic pain and highlights the need for further investigation with well-designed clinical trials. There is a significant lack of evidence indicating that cannabinoids administered by routes other than oral or inhaled may be an effective alternative, with better tolerance and safety in the treatment of neuropathic pain. Higher quality, long-term, randomized controlled trials are needed to examine whether cannabinoids administered by routes other than inhalation and oral routes may have a role in the treatment of neuropathic pain.